Combination of palmoplantar keratoderma and hair shaft anomalies, the warning signal of severe arrhythmogenic cardiomyopathy: a systematic review on genetic desmosomal diseases. Issue 5 (23rd September 2015) - Polivka, Laura; Bodemer, Christine; Hadj-Rabia, Smail
Abstract : Inherited desmosomal diseases are characterised by skin and/or cardiac features. Dermatological features might be a clue in the determination of the underlying life-threatening cardiac disease. This article aims to propose a dermatological algorithm for the diagnosis of desmosomal diseases after a systematic review of published articles. Palmoplantar keratoderma (PPK), hair shaft anomalies and skin fragility are the major features in the 458 patients analysed. Isolated PPK or isolated hair shaft anomalies are associated with a desmosomal disease limited to skin. The combination of PPK and hair shaft anomalies was recorded in 161 patients, and this association is at high risk of cardiac disease (129/161, 80.1%). Skin features had led to cardiac monitoring in only 2.3% of those patients. We delineated three major phenotypes: the PPK–hair shaft anomalies–non-fragile skin subtype (77%), always associated with cardiac involvement; the PPK–hair shaft anomalies–skin fragility–normal cardiac function subtype (19.9%), frequently associated with PKP1 mutations; the PPK–hair shaft anomalies–skin fragility–cardiac involvement subtype (3.1%), always due to DSP mutations. Three mutation hotspots in DSP and JUP account for 90.8% of the patients with cardiac involvement. The combination of PPK and hair shaft anomalies justifies long-term cardiac monitoring.